Molten pool behaviour and its physical mechanism during selective laser melting of TiC/AlSi10Mg nanocomposites: simulation and experiments. (5th January 2015) - Yuan, Pengpeng; Gu, Dongdong
Abstract: Simulation of temperature evolution and thermal behaviour of the molten pool during selective laser melting (SLM) of TiC/AlSi10Mg nanocomposites was performed, using a finite volume method. Some important physical phenomena, such as a transition from powder to solid, nonlinearities produced by temperature-dependent material properties and fluid flow, were taken into account in the calculation. The effects of Marangoni convection and SLM processing parameters, such as laser power and scan speed, on temperature evolution behaviour, molten pool dimensions and liquid lifetime were thoroughly investigated. The simulation results showed that Marangoni convection played a crucial role in intensifying the convective heat transfer and changing the molten pool geometry. The temperature of laser–powder interaction zone, the molten pool dimensions and liquid lifetime increased with increasing laser power or decreasing scan speed. The maximum temperature gradient within the molten pool increased significantly with increasing the applied laser power, but increased slightly as a higher scan speed was applied. The experimental study on the interlayer bonding and densification behaviour and the surface morphologies and balling effect of the SLM-processed TiC/AlSi10Mg nanocomposites parts was performed. The experimental results validated the thermal behaviour and underlying physical mechanism of the molten pool obtained in the simulations.